Problemy i perspektywy współczesnego ładu w handlu światowym - Sauernheimer, Karl-Hans (Digitalizacja i deponowanie archiwalnych zeszytów RPEiS sfinansowane przez MNiSW w ramach realizacji umowy nr 541/P-DUN/2016, 1990)
The article refers to the most important problems of contemporary international economic relations, with special attention paid to the causes and consequences of growing protectionistic and discriminatory tendencies in international trade. The growth of protectionism is the outcome of growing competition on the part of Japan and newly industralized countries as well as of instability of monetary conditions. Over- and undervalue of currencies give rise to employment problems and difficulties in balances of payment, leading to the intensification of protectionistic trade policy and to the growth of restrictions in international trade exchange. The analysis of the problems of contemporary order in world trade in regional and branch aspects leads to several conclusions. Firstly, administrative methods of control and stabilization of export income and prices in developing countries are for the most part inefficient Developing countries may gain more profit from liberalization rather than regulation of trade. Secondly, if the socialist countries introduce appropriate changes in their economies, they may achieve profits from the specialization of production also by increasing their "openness". Thirdly, agricultural and textile sectors belong to the most "regulated" ones. Reducing the degree of regulation of these two sectors is difficult not only because basic controversies occur between developed and developing countries but also among the countries belonging to the first of the two groups. The increase in prospective efficiency of GATT makes it necessary to adjust its rules to contemporary tendencies in international economic relations. In particular, it is indispensable to coordinate financial and monetary aspects of macroeconomic policy between main trade and political organizations. Moreover, structural adjustment of developed countries in traditional sectors is also indispensable. GATT should also provide for the exceptions to its own rules in order to present the development of uncontrolled restrictive regulations in international exchange.
Problems and perspectives of contemporary order in world trade